Associations of osteoporosis and sarcopenia with frailty and multimorbidity among participants of the Hertfordshire Cohort Study. Issue 1 (6th December 2021) - Laskou, Faidra; Fuggle, Nicholas R.; Patel, Harnish P.; Jameson, Karen; Cooper, Cyrus; Dennison, Elaine
Abstract: Background: Ageing is commonly associated with sarcopenia (SP) and osteoporosis (OP), both of which are associated with disability, impaired quality of life, and mortality. The aims of this study were to explore the relationships between SP, OP, frailty, and multimorbidity in community‐dwelling older adults participating in the Hertfordshire Cohort Study (HCS) and to determine whether coexistence of OP and SP was associated with a significantly heavier health burden. Methods: At baseline, 405 participants self‐reported their comorbidities. Cut‐offs for low grip strength and appendicular lean mass index were used according to the EWSGOP2 criteria to define SP. OP was diagnosed when T ‐scores of < −2.5 were present at the femoral neck or the participant reported use of the anti‐OP medications including hormone replacement therapy (HRT), raloxifene, or bisphosphonates. Frailty was defined using the standard Fried definition. Results: One hundred ninety‐nine men and 206 women were included in the study. Baseline median (interquartile range) age of participants was 75.5 (73.4–77.9) years. Twenty‐six (8%) and 66 (21.4%) of the participants had SP and OP, respectively. Eighty‐three (20.5%) reported three or more comorbidities. The prevalence of pre‐frailty and frailty in the study sample was 57.5% and 8.1%, respectively. Having SP only was strongly associated with frailty [odds ratio (OR) 8.28, 95% confidence interval (CI) 1.27, 54.03; P  = 0.027] while the association between having OP alone and frailty was weaker (OR 2.57, 95% CI 0.61, 10.78; P  = 0.196). The likelihood of being frail was substantially higher in the presence of coexisting SP and OP (OR 26.15, 95% CI 3.13, 218.76; P  = 0.003). SP alone and OP alone were both associated with having three or more comorbidities (OR 4.71, 95% CI 1.50, 14.76; P  = 0.008 and OR 2.86, 95% CI 1.32, 6.22; P  = 0.008, respectively) although the coexistence of SP and OP was not significantly associated with multimorbidity (OR 3.45, 95% CI 0.59, 20.26; P  = 0.171). Conclusions: Individuals living with frailty were often osteosarcopenic. Multimorbidity was common in individuals with either SP or OP. Early identification of SP and OP not only allows implementation of treatment strategies but also presents an opportunity to mitigate frailty risk.